Ongoing U snRNP Biogenesis Is Required for the Integrity of Cajal Bodies - Lemm, Ira (The American Society for Cell Biology, 2006)
Cajal bodies (CBs) have been implicated in the nuclear phase of the biogenesis of spliceosomal U small nuclear ribonucleoproteins (U snRNPs). Here, we have investigated the distribution of the CB marker protein coilin, U snRNPs, and proteins present in C/D box small nucleolar (sno)RNPs in cells depleted of hTGS1, SMN, or PHAX. Knockdown of any of these three proteins by RNAi interferes with U snRNP maturation before the reentry of U snRNA Sm cores into the nucleus. Strikingly, CBs are lost in the absence of hTGS1, SMN, or PHAX and coilin is dispersed in the nucleoplasm into numerous small foci. This indicates that the integrity of canonical CBs is dependent on ongoing U snRNP biogenesis. Spliceosomal U snRNPs show no detectable concentration in nuclear foci and do not colocalize with coilin in cells lacking hTGS1, SMN, or PHAX. In contrast, C/D box snoRNP components concentrate into nuclear foci that partially colocalize with coilin after inhibition of U snRNP maturation. We demonstrate by siRNA-mediated depletion that coilin is required for the condensation of U snRNPs, but not C/D box snoRNP components, into nucleoplasmic foci, and also for merging these factors into canonical CBs. Altogether, our data suggest that CBs have a modular structure with distinct domains for spliceosomal U snRNPs and snoRNPs.